2021
DOI: 10.1186/s12958-021-00816-y
|View full text |Cite
|
Sign up to set email alerts
|

HOX cluster and their cofactors showed an altered expression pattern in eutopic and ectopic endometriosis tissues

Abstract: Endometriosis is major gynecological disease that affects over 10% of women worldwide and 30%-50% of these women have pelvic pain, abnormal uterine bleeding and infertility. The cause of endometriosis is unknown and there is no definite cure mainly because of our limited knowledge about its pathophysiology at the cellular and molecular levels. Therefore, demystifying the molecular mechanisms that underlie endometriosis is essential to develop advanced therapies for this disease. In this regard, HOX genes are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The Lactate concentrations were as well in the long run selected in the peritoneal fluid of patients with EM [38]. At the same time, the related proteomic analysis found that ectopic endometrial stromal cells have extensive metabolic reprogramming and cancer-like changes, which have striking similarities with tumorigenesis [35,39,40]. Interestingly, the glycolysis inhibitor reduces the mouse peritoneal fluid lactate concentration and the size of endometriotic lesions in the mouse model of EM [37].…”
Section: Discussionmentioning
confidence: 91%
“…The Lactate concentrations were as well in the long run selected in the peritoneal fluid of patients with EM [38]. At the same time, the related proteomic analysis found that ectopic endometrial stromal cells have extensive metabolic reprogramming and cancer-like changes, which have striking similarities with tumorigenesis [35,39,40]. Interestingly, the glycolysis inhibitor reduces the mouse peritoneal fluid lactate concentration and the size of endometriotic lesions in the mouse model of EM [37].…”
Section: Discussionmentioning
confidence: 91%
“…Initially, the analysis of general data and clinic characteristics of EMT patients and healthy women unraveled the elevated proportions of dysmenorrhea, infertility, and pelvic pain in EMT patients. EMT individuals usually have a prolonged history of dysmenorrhea [31], and 30-50% of women with EMT also suffer from pelvic pain and infertility [32]. These clinical parameters could assist the diagnosis of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of the HOXC cluster has been found in ectopic and eutopic tissues from endometriosis patients vs. control 71-73 , as well as in gastrointestinal disorders such as ulcerative colitis, colorectal cancer and gastric cancer 74-77 . Even though RERG , and nearby PTPRO , were not implicated in any GWAS studies of the separate traits, P-values for the lead SNP were close to genome-wide significance ( P Endometriosis = 9.24E-06, P GPM = 8.80E-07) suggesting the increased power from combining the traits was able to identify a novel risk locus for both diseases.…”
Section: Discussionmentioning
confidence: 99%